A quality by design approach for the optimization of olmesartan medoxomil-orodispersible lyophilisates: In vitro/in vivo evaluation - Shereen H. Noshi, Marwa H. S. Dawoud, Mervat S. Ibrahim (Journal of Applied Pharmaceutical Science, 2022)
The current study aims to develop orodispersible lyophilisates (ODLs), containing olmesartan medoxomil (OLM), by applying a quality by design approach to ensure product robustness. A thorough risk assessment study was done, where the effects of each of the types of matrix former and superdisintegrant were assessed on the drug content, friability %, cumulative drug released within 15 minutes (Q15%), disintegration time, and wetting time. This was followed by a D-optimal design, for the optimization of the ODL. The optimization study focused on studying the effects of the solubilizer concentration (X1 ) and solubilizer type (X2 ) on the disintegration time (Y1 ) and Q15% (Y2 ). A design space was created with an optimized formula, OLM-ODL, which was prepared and tested to indicate the validity of the design. The optimized formula showed fast drug release with a short disintegration time. Further characterization tests were done on OLM-ODL, as morphological examination, which showed a highly porous nature. Infrared spectroscopy showed no incompatibility. The extent of OLM absorption from the optimized ODL compared to oral OLM suspension from a pharmacokinetic study. The ODL showed an enhancement of the relative bioavailability of the optimized formula of about 345%. Thus, ODLs were successfully developed using a quality by design approach with noticeably improved biopharmaceutical performance.
Keywords: Olmesartan medoxomil, Soluplus, orodispersible lyophilisates, Ishikawa diagram, quality target product profile